Factors Associated With Refractoriness to an Up to Fourfold Dosage of Antihistamines in Isolated Chronic Spontaneous Urticaria - Wongjirattikarn R. (2023)
Background: Chronic spontaneous urticaria (CSU) is a common skin disease and has a significant impact on patients’ quality of life. The aim of treatment is complete symptom control. Aim: To identify potential factors associated with antihistamine-refractory isolated CSU and to determine the factors that predict response to second-generation H1 antihistamines at dosages from one- to fourfold. Methods: We conducted a retrospective cohort study, which included adult patients diagnosed with isolated CSU and had complete symptom control. Clinical and laboratory findings were compared between the patients who were responsive to second-generation H1 antihistamines (< fourfold) and those who were refractory to a fourfold dose. Clinical and laboratory data were compared by dosage in the antihistamine-responsive group. Results: There were 182 isolated CSU patients who met the study criteria, of whom 150 (82.4%) were responsive to treatment with up to a fourfold dose of second-generation H1 antihistamines, while 32 (17.6%) were refractory. In univariate analysis, age at onset, body mass index, baseline Urticaria Activity Score-7 (UAS7), white blood cell count, total neutrophil count, neutrophil-lymphocyte ratio, platelet count, and new generation antihistamines were significantly higher in the antihistamine-refractory group. According to multivariate analysis, baseline UAS7 was the only independent factor associated with antihistamine-refractory isolated CSU (odds ratio 1.14, 95% CI 1.01-1.28, P =.03). In the antihistamine-responsive group, white blood cell count tended to predict response to antihistamine treatment (P <.001, 0.04, 0.34 between onefold and twofold, twofold and threefold, and threefold and fourfold, respectively). Conclusion: Baseline UAS7 was an independent factor associated with antihistamine-refractory isolated CSU.